Shariah Fintech And Islamic Economic Sustainability: An Integrative Analysis Between Technology And Maqasid Al-Syari'ah - Desy Arum Sunarta; Syaripuddin; Nelia Sfayriawati; Jamaluddin Majid (PT. Gudang Pustaka Cendekia, 2025)
This study aims to analyze the role of innovation and technology in strengthening the Islamic finance ecosystem in the digital era. The research employs a qualitative-descriptive approach through a literature-based analysis integrating technology adoption theories (TAM, UTAUT, DOI) and the principles of maqaṣid al-shari’ah as the theoretical foundation. The findings reveal that perceived usefulness, ease of use, social influence, and infrastructural support are the key determinants influencing users’ intentions toward adopting Islamic financial technologies. Furthermore, Shariah-compliant fintech innovation driven by maqaṣid al-shari’ah enhances financial inclusion, ethical governance, and sustainable economic development. The study emphasizes that collaboration among regulators, financial institutions, and educational entities is crucial to developing adaptive regulations and strengthening digital-Shariah literacy. The main conclusion underscores the significance of aligning technological innovation with Islamic ethical principles to advance the competitiveness of the Islamic finance industry globally.